Safety, Pharmacokinetics, and Pharmacodynamics of Multiple Rising Doses of BI 655064, an Antagonistic Anti‐CD40 Antibody, in Healthy Subjects: A Potential Novel Treatment for Autoimmune Diseases - Schwabe, Christian; Rosenstock, Bernd; Doan, Thi; Hamilton, Paul; Dunbar, P. Rod; Eleftheraki, Anastasia G.; Joseph, David; Hilbert, James; Schoelch, Corinna; Padula, Steven J.; Steffgen, Jürgen (Journal of clinical pharmacology, 2018)
BI 655064 is a humanized antagonistic anti‐cluster of differentiation (CD) 40 monoclonal antibody that selectively blocks the CD40‐CD40L interaction. The CD40‐CD40L pathway is a promising treatment target for autoimmune diseases such as rheumatoid arthritis, systemic lupus erythematosus, and lupus nephritis. The safety, tolerability, pharmacokinetics, and pharmacodynamics of repeated once‐weekly BI 655064 subcutaneous dosing over 4 weeks were evaluated in a multiple‐dose study in healthy subjects. Subjects (N = 40) were randomized 4:1 to four sequential BI 655064 dose groups (80, 120, 180, 240 mg) or to placebo. Safety and tolerability, plasma exposure, CD40 receptor occupancy, and CD40L‐induced CD54 upregulation were assessed over 64 and 78 days for the 80‐ to 180‐mg and 240‐mg dose groups, respectively. BI 655064 exposure increased in a supraproportional manner, due to target‐mediated drug clearance, for doses between 80 mg and 120 mg, but was near proportional for doses greater than 120 mg. Terminal half‐life ranged between 6 and 8 days. Dose‐dependent accumulation of BI 655064 supports the use of a loading dose in future clinical studies. Following 4 weeks of dosing, >90% CD40 receptor occupancy and inhibition of CD54 upregulation were observed at all dose levels, lasting for 17 days after the last dose. BI 655064 was generally well tolerated. There were no serious adverse events and the frequency and intensity of adverse events were similar for BI 655064 and placebo; no dose relationship or relevant signs of an acute immune reaction were observed. These findings support further investigation of BI 655064 as a potential treatment for autoimmune diseases.